Unsteady aerodynamics on a tapered prism under forced excitation. (1st August 2021) - Chen, Zengshun; Huang, Hailin; Xu, Yemeng; Tse, K.T.; Kim, Bubryur; Wang, Yatai
Highlights: A forced vibration test carried out to obtain unsteady aerodynamic forces on a tapered prism. Unsteady aerodynamics on a tapered prism analyzed. Aerodynamic damping of a tapered prism identified. Abstract: Tapered buildings have been widely built in recent years and its aerodynamic performance remains unclear and would be much different from that on traditional buildings. In this paper, unsteady pressures on a tapered test model under different wind speeds and amplitudes of oscillation were sampled during forced vibrations. Wind pressure distributions and unsteady force coefficients on the test model were analyzed. It demonstrated that the root mean square lift coefficient increases significantly with amplitudes of oscillation at low wind speeds, while at high wind speeds, the influence of structural oscillation is significantly reduced and the aerodynamic force is in a quasi-static state. This conclusion was discussed and confirmed in the subsequent analysis of power spectral densities and Strouhal numbers. Finally, the aerodynamic damping of the test model was identified and the effects of wind speed and amplitude of oscillation on the result were analyzed. This study has not only advanced our understanding of unsteady aerodynamic characteristics on tapered prisms, but provided a forced vibration test technique used in wind tunnel.